Assessing the ability of Pleiades stereo imagery to determine height changes in earthquakes: A case study for the El Mayor‐Cucapah epicentral area. Issue 12 (28th December 2015) - Zhou, Yu; Parsons, Barry; Elliott, John R; Barisin, Ivana; Walker, Richard T
Abstract: High‐resolution surface topography is valuable for studying coseismic fault zone deformation and fault geometry. It enables us to measure three‐dimensional surface displacements in earthquakes, as shown in recent studies that used light detection and ranging (lidar) to determine coseismic motion. However, the applicability of lidar is limited by its relatively high cost and low availability. In this study, we use the 2010 El Mayor‐Cucapah earthquake to demonstrate the capability of Pleiades stereo imagery to measure coseismic vertical ground displacement. We acquired post‐earthquake Pleiades tristereo imagery from backward, near‐nadir, and forward orientations for a 45 km × 7 km portion of the epicentral area. One meter resolution digital elevation models (DEMs) were produced with the four different combinations of incidence angles and compared to the post‐earthquake lidar DEM. Elevations from tristereo have slightly (∼15%) smaller uncertainties than bistereo as the tristereo DEM incorporates more observations. Elevation differences between the Pleiades and post‐earthquake lidar DEMs show that the vertical accuracy of the Pleiades DEMs is ∼0.3 m. By differencing the Pleiades DEM and the pre‐earthquake, 5 m resolution lidar DEM, we mapped meter and submeter offsets along the faults obtaining results comparable to a previous study that differenced the two lidar DEMs. This is the first case study of assessing very high resolution (VHR) satellite stereo imagery to determine submeter vertical ground displacement in an earthquake. By extension, we expect it to be possible to measure submeter vertical offsets occurring in earthquakes using pre‐earthquake and post‐earthquake VHR stereo imagery. Key Points: First case study of assessing VHR stereo imagery to determine height changes in an earthquake Elevations from tristereo have slightly (∼15%) smaller uncertainties than bistereo Coseismic height changes mapped using the Pleiades DEM are comparable to differential lidar